DIFFICULTIES OF ELEMENTARY SCHOOL GRADE VI SOLVING NARRATIVE TEST IN NUMBER MATERIAL - Ragil Tri Lestari; Siti Khabibah (Program Studi S1 Matematika UNESA, 2022)
Mathematics is one of the sciences closely related to human life in helping to solve a problem. Narrative tests are a type of question that is suitable for use in presenting a mathematical problem. When solving narrative testss, difficulties are often found. This study aims to describe the difficulties experienced by students in solving narrative tests. The type of this research is qualitative research, with the research subjects being 12 sixth grade students who have the various mathematical abilities in one of the elementary schools in Gresik. Data collection through written tests, interviews, and documentation. The results showed that students experienced difficulties in three aspects, namely: 1) language aspects. Broadly speaking, students' difficulties in language aspects were caused by a lack of understanding of narrative testss, 2) schematic knowledge aspects, this difficulty was triggered because students were unable to remember and use mathematical concepts well, and 3) the algorithm aspect, this difficulty is caused by students doing the calculation process in a hurry. Narrative tests with simple context and language regularly can be done as an alternative to minimize the level of difficulty of students and help students build a more structured way of thinking. Keywords: qualitative research, difficulties, narrative tests.